Great tits differ in glucocorticoid plasticity in response to spring temperature. Issue 1986 (9th November 2022) - Hau, Michaela; Deimel, Caroline; Moiron, Maria
Abstract : Fluctuations in environmental temperature affect energy metabolism and stimulate the expression of reversible phenotypic plasticity in vertebrate behavioural and physiological traits. Changes in circulating concentrations of glucocorticoid hormones often underpin environmentally induced phenotypic plasticity. Ongoing climate change is predicted to increase fluctuations in environmental temperature globally, making it imperative to determine the standing phenotypic variation in glucocorticoid responses of free-living populations to evaluate their potential for coping via plastic or evolutionary changes. Using a reaction norm approach, we repeatedly sampled wild great tit ( Parus major ) individuals for circulating glucocorticoid concentrations during reproduction across five years to quantify individual variation in glucocorticoid plasticity along an environmental temperature gradient. As expected, baseline and stress-induced glucocorticoid concentrations increased with lower environmental temperatures at the population and within-individual level. Moreover, we provide unique evidence that individuals differ significantly in their plastic responses to the temperature gradient for both glucocorticoid traits, with some displaying greater plasticity than others. Average concentrations and degree of plasticity covaried for baseline glucocorticoids, indicating that these two reaction norm components are linked. Hence, individual variation in glucocorticoid plasticity in response to a key environmental factor exists in a wild vertebrate population, representing a crucial step to assess their potential to endure temperature fluctuations.